👤

factoriser au maximum:

a) (x+2)(6x-3)-(1-2x)^2
b) x^2 (x+1) - x -1
c) (10x-5)(x+2)+(1-x)(2x-1)


Répondre :

Bonsoir

factoriser au maximum:

a) A = (x+2)(6x-3)-(1-2x)²

A = (x+2)(6x-3)-(1-2x)(1 - 2x)

A = (x+2)(6x-3)-(1-2x)( (-1) (- 1 + 2x) )

A = (x+2)(6x-3) + (1-2x)(- 1 + 2x)

A = (x+2)(3× 2x-3 × 1) + (1-2x)( 2x - 1)

Le facteur commun est ici souligné.

On le met devant et on met tout le reste derrière.

A = 3 (x+2)( 2x- 1) + (1-2x)( 2x - 1)

Le facteur commun est ici souligné.

On le met devant et on met tout le reste derrière.

A = (2x- 1) (3 (x+2) + (1-2x) )

A = (2x- 1) (3 (x+2) + (1-2x) )

A = (2x- 1) (3 x + 6 + 1 - 2x )

A = (2x- 1) ( x + 7 )

___________________________________________________

b)B =  x² (x+1) - x -1

B = x² (x+1) + (- 1) ( x  + 1 )

B = x² (x+1) - (1) ( x  + 1 )

Le facteur commun est ici souligné.

On le met devant et on met tout le reste derrière.

B =  ( x  + 1 ) (x²- 1)

________________________________________________________

c) C = (10x-5)(x+2)+(1-x)(2x-1)

C = (5 × 2x-5 × 1 )(x+2)+(1-x)(2x-1)

Le facteur commun est ici souligné.

On le met devant et on met tout le reste derrière.

C = 5 (2x- 1 )(x+2)+(1-x)(2x-1)

Le facteur commun est ici souligné.

On le met devant et on met tout le reste derrière.

C = (2x- 1 )( 5(x+2)+(1-x) )

C = (2x- 1 )( 5x+ 10 + 1 - x )

C = (2x- 1 )( 4x + 11)